The relations between adolescents` personal values and prosocial and antisocial behaviours in team sports - Danioni, F.; Barni, D. (International Journal of Sport and Exercise Psychology, 2019)
This study examines adolescents` personal values within the sport context, and the connection between those values and pro- and antisocial behaviours towards teammates and opponents on the part of young players. To measure these variables, we administered the 21-item Portrait Values Questionnaire and the Prosocial and Antisocial Behavior in Sport Scale to 172 team sports athletes between 13 and 19 years of age. Findings showed that young players attributed the greatest importance to self-transcendence values and the least importance to self-enhancement values. Values were significantly related to adolescents` prosocial and, to a greater degree, antisocial behaviours. In particular, antisocial behaviours were positively related to values of self-enhancement and openness to change, but were discouraged by values related to self-transcendence and conservation. Interestingly, the relationship between values of self-transcendence and openness to change and antisocial behaviour towards teammates, and that between values of self-enhancement and antisocial behaviour towards opponents were moderated by parental pressure towards their children in sport. Parental pressure also moderated the relationship between conservation values and openness to change and prosocial behaviour towards teammates. Implications and further expansion of the study are discussed.